What is at stake in building "non-western" international relations theory? - Eun, Yong-Soo (IR theory and practice in Asia ;, 2018)
"International Relations (IR) as a discipline is often deemed to be 'too Western' centric. It has been argued that much of mainstream IR theory is 'simply an abstraction of Western history.' In this respect, many IR scholars have called for 'broadening' the theoretical horizon of IR while problematising the Western parochialism of the discipline, and it is increasingly acknowledged that IR needs to embrace a wider range of histories, experiences, and theoretical perspectives, particularly those outside of the West.